The attitude of elderly lay people towards the symptoms of dementia - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2006)
Objectives: To assess the attitude of elderly lay people towards the concept and symptoms of dementia. Methods: A population-based, cross-sectional study of 859 residents without dementia, aged 70 years or older, living in an urban area in Istanbul. Nine questions with yes/no responses were designed to investigate the attitudes of the responders to the concept of dementia and symptoms related to particular aspects of dementia. The chi(2)-test was used to test for differences between proportions of respondents in different age, sex and education groups. Results: Dementia was considered as normal by the majority of respondents and age and education did not influence this attitude. Women were significantly less inclined to consider dementia and its associated problems as normal. Conclusion: The concept of dementia is generally not considered as a medical problem by the elderly Turkish population, independent of age and education. These results are important in guiding policy makers and shaping awareness raising campaigns of local Alzheimer's Associations.
Keywords: dementia; attitude; aging; RISK-FACTORS; PERCEPTIONS; POPULATION